2023
DOI: 10.1002/cam4.5675
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of alanyl aminopeptidase is a robust biomarker of non‐familial adenomatous polyposis and non‐hereditary nonpolyposis colorectal cancer syndrome early‐onset colorectal cancer

Abstract: Background Early‐onset colorectal cancer (EOCRC) has been increasing in incidence worldwide but its genomic pathogenesis is mostly undetermined. This study aimed to identify robust EOCRC‐specific gene expression patterns in non‐familial adenomatous polyposis (FAP) and non‐hereditary nonpolyposis colorectal cancer syndrome (HNPCC) EOCRC. Method We first performed gene expression profiling analysis using RNA sequencing of discovery cohort comprised of 49 EOCRC (age <50) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Other studies have found no such differences (17) and instead found differences in DNA damage response (17) or oxidative stress response (18). Some studies have implicated specific genes involved in EOCRC such as ALDH1A1 (19,20), PEG10 (21), or ANPEP (22). Many previous EOCRC transcriptomic studies examine differences between EOCRC and LOCRC tumor samples (19,(21)(22)(23), leaving it unclear whether results are important for cancer progression or artifacts of aging tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found no such differences (17) and instead found differences in DNA damage response (17) or oxidative stress response (18). Some studies have implicated specific genes involved in EOCRC such as ALDH1A1 (19,20), PEG10 (21), or ANPEP (22). Many previous EOCRC transcriptomic studies examine differences between EOCRC and LOCRC tumor samples (19,(21)(22)(23), leaving it unclear whether results are important for cancer progression or artifacts of aging tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have implicated specific genes involved in EOCRC such as ALDH1A1 (19,20), PEG10 (21), or ANPEP (22). Many previous EOCRC transcriptomic studies examine differences between EOCRC and LOCRC tumor samples (19,(21)(22)(23), leaving it unclear whether results are important for cancer progression or artifacts of aging tissues. Other studies may have matched control samples but do not control for patient characteristics between EOCRCs and LOCRCs (17), allowing for differences between patient populations, such as stage, gender, tumor location, and histology, to drive EOCRC versus LOCRC differences (13).…”
Section: Introductionmentioning
confidence: 99%